EFFECTIVENESS OF UMKM CULINARY PRODUCTS IN INCREASING COMPETITIVENESS IN DEPOK CITY - Anak Agung Gede Ajusta; Wawan Ridwan; Slamet Maryoso; Ernawati Ernawati; Nanang Lidwan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play an important role in local economic development. The city of Depok has experienced rapid growth in culinary MSMEs but faces challenges in competition, innovation, and marketing. This study aims to analyze the effectiveness of culinary MSME products in improving competitiveness and customer satisfaction. A quantitative method was used with survey data analyzed using multiple and simple regression. The results show that product quality, innovation, price, and marketing strategy significantly influence product effectiveness. Product effectiveness also significantly affects customer satisfaction.